An assessment of Inventory Models Utilizing Fuzzy Theory: An application and approaches (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Inventory management plays a crucial role in the operational efficiency and profitability of businesses. Traditional inventory models often rely on precise data, which may not accurately reflect the inherent uncertainties in demand, supply, and lead times. This paper explores the integration of fuzzy theory into inventory models to better accommodate and manage these uncertainties. By employing fuzzy logic, the study enhances the robustness of inventory decisions, leading to improved service levels and reduced costs. The research includes a comprehensive review of existing literature, the development of a fuzzy-based inventory model, and a comparative analysis with classical models. The findings suggest that fuzzy inventory models offer significant advantages in handling imprecise information, thereby providing more flexible and realistic solutions for inventory management.